La nutrición infantil y su incidencia en el rendimiento escolar de los niños y niñas del primer año de educación básica del plantel central Dr. Alfredo Pérez Guerrero de la ciudad de Santa Rosa en el periodo lectivo 2012-2013. - Aponte Córdova, Bélgica Elizabeth (2013)
Almost all studies of Nutrition conducted in school-age children, yes based primarily on the assessment of body growth through several anthropometric measurements, alone to establish with enough approximation if there is a normal physical growth, or conversely, the one delay or acceleration in the growth rate.